Spatial and temporal conversion of nitrogen using Arthrobacter sp. 24S4–2, a strain obtained from Antarctica - Liu, Yixuan; Zhang, Yumin; Huang, Yudi; Niu, Jingjing; Huang, Jun; Peng, Xiaoya; Peng, Fang (Frontiers in Microbiology, 2023)
According to average nucleotide identity (ANI) analysis of the complete genomes, strain 24S4–2 isolated from Antarctica is considered as a potential novel Arthrobacter species. Arthrobacter sp. 24S4–2 could grow and produce ammonium in nitrate or nitrite or even nitrogen free medium. Strain 24S4–2 was discovered to accumulate nitrate/nitrite and subsequently convert nitrate to nitrite intracellularly when incubated in a nitrate/nitrite medium. In nitrogen-free medium, strain 24S4-2 not only reduced the accumulated nitrite for growth, but also secreted ammonia to the extracellular under aerobic condition, which was thought to be linked to nitrite reductase genes nirB, nirD, and nasA by the transcriptome and RT-qPCR analysis. A membrane-like vesicle structure was detected in the cell of strain 24S4–2 by transmission electron microscopy, which was thought to be the site of intracellular nitrogen supply accumulation and conversion. This spatial and temporal conversion process of nitrogen source helps the strain maintain development in the absence of nitrogen supply or a harsh environment, which is part of its adaption strategy to the Antarctic environment. This process may also play an important ecological role, that other bacteria in the environment would benefit from its extracellular nitrogen source secretion and nitrite consumption characteristics.